Efektivitas Penggunaan Media Manipulatif melalui Pendekatan RME untuk Meningkatkan Kemampuan Berhitung Siswa SD/MI - Navila Dwi Irmayani; Hustriasa Niswatun; Afnis Iis Munandar; Djuita Hidayati (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The aim of this research is to explore the use of manipulative media through a realistic mathematics education (RME) approach in improving students' numeracy skills at MI Nurul Islam. This research uses a qualitative descriptive method and includes observation and interviews as data collection techniques. This research was conducted by students at the Mataram State Islamic University. The research was located at MI Nurul Islam, Sekarbela sub-district, Mataram city. To be precise, for class I teachers, researchers also analyzed the data using qualitative analysis. Research findings show that the use of manipulative media through the RME approach can improve students' comprehension and numeracy skills. students become more engaged in learning, and see improvements in their problem-solving numeracy skills. Manipulative media can also help reduce calculation errors and increase students' confidence in learning mathematics. Based on these results, it is concluded that the use of manipulative media through the RME approach is effective in improving the numeracy skills of MI Nurul Islam students and can be an alternative strategy in learning mathematics at the elementary level.